Patients' Preferences for 3 Months vs 6 Months of Adjuvant Chemotherapy for Colon Cancer. Issue 1 (28th November 2020) - Blinman, Prunella; Martin, Andrew; Jefford, Michael; Goldstein, David; Boadle, David; Morris, Michelle; Tebbutt, Niall; Aiken, Christine; Harkin, Andrea; Segelov, Eva; Haydon, Andrew; Iveson, Tim; et al.
Abstract: Background: SCOT was an international, randomized phase 3 trial of 3 months vs 6 months of adjuvant chemotherapy with oxaliplatin and a fluoropyrimidine in patients with colorectal cancer. We sought patients' preferences for 3 months vs 6 months of adjuvant chemotherapy in the SCOT trial. Methods: SCOT participants from Australia and New Zealand completed a validated questionnaire (at 3 and 18 months) to elicit the minimum survival benefits judged necessary to make an extra 3 months of adjuvant chemotherapy worthwhile, based on their experience. Standardized hypothetical scenarios used the following baseline survivals (with 3 months of chemotherapy): life expectancies (LE) of 5 years and 15 years and 5-year survival rates (5YS) of 65% and 85%. Results: Of the 160 participants, 82 were assigned 3 months adjuvant chemotherapy, and 78 were assigned 6 months. Adjuvant chemotherapy was FOLFOX in 121 (75.6%) and XELOX in 39 (24.4%). Preferences varied substantially and did not differ according to treatment group. The median survival benefits judged necessary to make the extra 3 months of chemotherapy worthwhile were an extra 3 years beyond a LE of 5 years; 3 years beyond a LE of 15 years; 15% beyond a 5YS of 65%; and 5% beyond a 5YS of 85%. Preferences were similar at 3 months and 18 months. Preferences were not predicted by participants' baseline characteristics. Conclusion: Preferences varied substantially, and the benefits many required to warrant an extra 3 months of adjuvant chemotherapy were larger than the benefits of an extra 3 months of chemotherapy calculated in the International Duration Evaluation of Adjuvant Chemotherapy (IDEA) meta-analysis.